Mesenchymal stem cell therapies in brain disease. (November 2019) - Sherman, Lauren S.; Romagano, Matthew P.; Williams, Shauna F.; Rameshwar, Pranela
Abstract: As treatments for diseases throughout the body progress, treatment for many brain diseases has been at a standstill due to difficulties in drug delivery. While new drugs are being discovered in vitro, these therapies are often hindered by inefficient tissue distribution and, more commonly, an inability to cross the blood brain barrier. Mesenchymal stem cells are thus being investigated as a delivery tool to directly target therapies to the brain to treat wide array of brain diseases. This review discusses the use of mesenchymal stem cells in hypoxic disease (hypoxic ischemic encephalopathy), an inflammatory neurodegenerative disease (multiple sclerosis), and a malignant condition (glioma).